Pesquisa em educação médica conduzida por estudantes: um ano de experiência do Núcleo Acadêmico de Pesquisa em Educação Médica - Hamamoto Filho, Pedro Tadao [UNESP]; Venditti, Vinicius Cunha [UNESP]; Miguel, Licério [UNESP]; Silva, Ludmila Almeida [UNESP]; Oliveira, Cristiano Claudino [UNESP]; Peraçoli, José Carlos [UNESP] (FapUNIFESP (SciELO), 2011)
Research on medical education has expanded in recent years. Students’ participation in curriculum change has also increased, with major contributions. Initiation in scientific research has also been widely defended due to its positive impact on professional training. We report on the one-year experience at the Academic Center for Research in Medical Education (NAPEM), which incorporates proposals for student participation in discussions on medical teaching through scientific initiation projects in medical education. Founded in 2008, NAPEM was well-received by the academic community at the Botucatu School of Medicine/São Paulo State University (FMB/UNESP). Its current research projects focus on the evaluation of the course in medicine, student evaluation, factors influencing the search for scientific initiation, Student Leagues, and interdisciplinary approaches. A total of 17 students and ten faculty members are involved. In one year, NAPEM has presented papers at congresses, published an article in an indexed journal, and is certified by the Brazilian National Research Council (CNPq). Its challenges include the need for constant renewal of students and progress in research projects, to keep the latter from becoming self-contained, but rather to serve as a continuum in research, to the extent that new findings are added to the body of knowledge on medical education.

A pesquisa em educação médica vem se desenvolvendo muito nos últimos anos. A participação de estudantes nos processos de mudanças curriculares também é crescente e bastante contributiva. Ainda, a iniciação científica está sendo amplamente defendida por seu impacto positivo na formação profissional. Relatamos um ano de experiência do Núcleo Acadêmico de Pesquisa em Educação Médica (Napem), que integra as propostas de participação discente nas discussões de ensino médico através de trabalhos de iniciação científica em educação médica. O Napem foi fundado em 2008 e foi bem aceito na comunidade acadêmica da Faculdade de Medicina de Botucatu/Universidade Estadual Paulista (FMB/Unesp). Seus projetos de pesquisa atuais investigam: avaliação do curso médico, avaliação do estudante, fatores que influenciam a busca por iniciação científica, Ligas Acadêmicas e interdisciplinaridade. Estão envolvidos 17 estudantes e dez professores. Em um ano, o Napem apresentou trabalhos em congressos, publicou artigo em periódico indexado e está certificado como grupo de pesquisa no CNPq. Dentre seus desafios estão a necessidade de contínua renovação dos estudantes e o avanço nas pesquisas, de modo que os projetos não se encerrem em si mesmos, mas constituam um continuum de investigação à medida que novas informações sejam agregadas ao conhecimento.
Research by students in medical education: a one-year experience at the Academic Center for Research in Medical Education
Keywords: Education, medical; Medical education research; Students, medical; Educação médica; Pesquisa em educação médica; Estudantes de medicina